COMBINED ASSOCIATION OF SLEEP DURATION AND SLEEP QUALITY WITH QUALITY OF LIFE IN TYPE 2 DIABETES PATIENTS. (11th November 2018) - Zeng, Y; Wu, J; Fang, Y
Abstract: Sleep problems are very common in elderly with diabetes. We analyzed the community-based cross-sectional data of 798 elderly patients with T2DM in Xiamen, China, in 2016. Sleep duration was measured as self-reported average sleep time during the previous month. Sleep quality was evaluated as self-rated reports. QOL was assessed by the Diabetes-specific Quality of Life (DSQL). Ordinal logistic regression was performed to model the associations of QOL with sleep duration, sleep quality, and their combined effects by adjusting for certain covariates.The separate associations of sleep duration and sleep quality in relation to QOL in T2DM patients were significant (P < 0.05). Under conditions of constant sleep quality, there was no significant correlation between sleep duration and QOL. The combined analysis suggested that the association of sleep duration with QOL in T2DM elderly patients was sleep quality-dependent. Longer sleep duration was associated with higher odds ratios (ORs) of better QOL for patients who reported fair sleep quality and good sleep quality, but no such trend was observed for patients who reported poor sleep quality (P>0.05). Excessive sleep duration (≥9 h per day) was detrimental to QOL in T2DM only when they reported poor sleep quality. Specific disparities exist in the association of sleep quality with sleep duration and QOL in T2DM elderly patients. Failure to take into account the effect of sleep quality when evaluating the impact of sleep on QOL may be detrimental to the QOL.